The Importance of Transparency in Halal Certification for Protecting Muslim Consumers - Musa, Salzabila; Krustiyati, Atik (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
As a country with a predominantly Muslim population, Indonesia has an obligation to protect Muslim consumers by ensuring the halal status of products circulating within the country. Law No. 8 of 1999 concerning Consumer Protection and Law No. 33 of 2014 concerning Halal Product Guarantee serve as legal instruments to protect Muslim consumers. However, several issues still arise in the implementation of transparency in halal certification. For instance, there are domestically and internationally produced halal-certified products circulating in Indonesia that are not truly halal because they contain porcine elements (pig-derived substances). This study aims to analyze the regulation of transparency in halal certification for food products as a form of protection for Muslim consumers. The research method used in this article is normative legal research. Data was collected through library studies, which include legislation and other regulations as primary data sources, as well as journal articles, books, and websites as secondary data sources. The approaches used include legislative, case, and conceptual approaches. The study’s results show that although halal certification transparency is regulated under positive law, it has not been optimally implemented, leaving loopholes that may harm Muslim consumers. Therefore, strong synergy between institutions, an increase in legal awareness among business actors, and more stringent law enforcement mechanisms are needed.